Stochastic harmonic function based wind field simulation and wind-induced reliability of super high-rise buildings. (1st November 2019) - Chen, Jianbing; Chen, Youwei; Peng, Yongbo; Zhu, Shiyun; Beer, Michael; Comerford, Liam
Highlights: The SHF-SRM is extended to the simulation of multi-variate random processes. Effectiveness of the SHF-SRM in simulating a large-size wind fluctuation field is proved. Reliability provides a metric for the logical wind-resistant design of super high-rise buildings. Abstract: Wind field simulation and wind-induced reliability assessment are two critical steps in wind-induced vibration analysis and design of super high-rise buildings. Owing to its simple algorithm and rigorous theoretical basis, the spectral representation method (SRM) is widely used in practice. However, the SRM still encounters the computational challenge due to the Cholesky decomposition with respect to the crossing-power spectral density (PSD) matrix, particularly in the simulation of multi-variate random processes of large-size wind fluctuation fields. To circumvent this challenge, the stochastic harmonic function based spectral representation method (SHF-SRM) proposed in recent years is extended to the simulation of multi-variate random processes. In conjunction with the probability density evolution method (PDEM), the stochastic response analysis and reliability assessment of wind-induced random vibration of structures is addressed. For illustrative purposes, the wind field simulation and wind-induced vibration and reliability assessment of a 417.7 m high building are carried out. The numerical example proves the effectiveness of the SHF-SRM in simulating multi-variate random processes, and reveals the value of reliability assessment in terms of the global reliability and the time-variant reliability for the enhancement of wind-resistant design of high-rise buildings.